A kind of polylactic acid composite material toughened by dynamic cross-linking polyurethane and preparation method thereof

By adding dynamic cross -linked polyurethane to polystumin and mixed preparation of high -temperature melting melting, the problem of poor tough effect, toxic volatilization and permanent cross -linking structure in existing technologies, realizing high toughness and low shrinkage polygunciation polygunciations Milky acid composite material.

CN116285312BActive Publication Date: 2025-01-28BEIJING UNIV OF CHEM TECH
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202310195321.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-03
Publication Date
2025-01-28
Estimated Expiration
2043-03-03

AI Technical Summary

Technical Problem

The existing polyurethane toughening polylactic acid technology has problems such as poor toughening effect, toxic and harmful volatiles in the process, and the mostly permanent crosslinked structure of rubber phases, resulting in shrinkage and dimensional errors in process products.

Method used

The dynamic cross -linked polyurethane tougher polystrackic acid composite material is used, and the dynamic key polyurethane is added to the polystumin, and the preparation of polyurethane is adjusted through high temperature melting melting to improve the toughness and processing performance of the composite material.

Benefits of technology

A significant improvement of the effect of toughening was achieved. The impact intensity of the gap reached 84.42kJ/m2, the contraction rate remained at 0.75%, close to pure polystraphic acid, and avoided the size errors caused by the existence of toxic hair and permanent cross -linking structure.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116285312B_ABST
    Figure CN116285312B_ABST
Patent Text Reader

Abstract

The invention provides a polylactic acid composite material toughened with dynamic bond polyurethane and a preparation method thereof. The polylactic acid is toughened and modified by using the polyurethane containing dynamic bonds, so that the dynamically cross-linked polyurethane toughened polylactic acid with good toughening effect and low environmental harm is obtained. Meanwhile, the technical scheme of the invention matches the existing industrial equipment and has a high prospect for industrial application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of polymer materials, and in particular relates to a polylactic acid composite material toughened with dynamic bond polyurethane and a preparation method thereof. Background Art

[0002] Traditional petroleum-based plastics, such as polyethylene and polypropylene, are made from petroleum resources. However, the reserves of petroleum resources are limited, and petroleum-based plastics are facing an unsustainable crisis. In addition, due to their stable chemical structure, traditional petroleum-based plastics are difficult to degrade in nature after being discarded, causing white pollution. In order to solve the two major problems of traditional petroleum-based plastics, the research on bio-based degradable plastics has continued to develop in depth.

[0003] Polylactic acid is a bio-based plastic that can be obtained by obtaining lactic acid monomers through microbial fermentation of biomass raw materials (such as starch, sucrose, etc.), and then through condensation polymerization. Polylactic acid has excellent mechanical strength, biocompatibility, and biodegradability. In addition, polylactic acid has a high degree of commercialization and its cost is lower than that of bio-based degradable plastics such as polyhydroxyalkanoates. It is currently the most promising product to replace traditional petroleum-based plastics. However, the poor toughness and low impact strength of polylactic acid itself limit its scope of application.

[0004] Researchers at home and abroad have carried out a lot of work on the research direction of toughening of polylactic acid. The current research mainly focuses on chemical copolymerization modification, physical blending modification, dynamic vulcanization modification, etc. Polyurethane elastomers are used in the research of toughening of polylactic acid due to their high strength and high controllability of performance. In the prior art, polylactic acid composites are also commonly prepared by high-temperature dynamic vulcanization of polyols, excess isocyanates and polylactic acid (such as patents CN108707322A and CN103450649A). This method can greatly improve the toughness of polylactic acid and reach the super-tough level (impact strength > 53KJ / m 2 ), but isocyanates such as hexamethylene diisocyanate and diphenylmethane diisocyanate will produce organic volatiles during high-temperature processing, thereby endangering the life and health of operators. In addition, high-temperature dynamic vulcanization cross-linking of eucommia gum, natural rubber, etc. with polylactic acid can also effectively improve the toughness of polylactic acid (such as patents CN112175365A and CN109401243A). However, the rubber materials in the above-mentioned technologies all form a permanent cross-linked structure. During the cooling process of injection molding, extrusion, blow molding, etc., the internal stress will lead to a higher shrinkage rate, resulting in a large deviation in product size and affecting accuracy.

[0005] The main problems existing in the existing polyurethane toughened polylactic acid technology are: 1. The toughening effect is poor and the toughness improvement is not obvious; 2. Toxic and harmful volatiles exist in the process, which endanger the health of operators; 3. The rubber phase in the high-toughness polylactic acid composite material is mostly a permanent cross-linked structure, and the existence of internal stress will cause the processed product to shrink and cause dimensional errors. Summary of the invention

[0006] In view of the problems existing in the existing technical solutions, the present invention provides a technical solution of dynamically cross-linked polyurethane toughened polylactic acid with good toughening effect and little environmental harm. At the same time, the technical solution of the present invention is compatible with existing industrial equipment and has a high prospect for industrial application.

[0007] One of the purposes of the present invention is to provide a dynamically cross-linked polyurethane toughened polylactic acid composite material, comprising: a mixture of polyurethane containing dynamic bonds, polylactic acid and / or a reaction product thereof.

[0008] Wherein, the dynamic bond in the dynamic bond-containing polyurethane is at least one of a dithioacetal bond, a disulfide bond, an imine bond, a β-hydroxy ester bond, a borate ester bond, a silyl ether bond, and a cyclic acetal bond;

[0009] The hard segment content of the dynamic bond-containing polyurethane is 10 to 50 wt%, preferably 20 to 30 wt%; the R value is 1.00;

[0010] In the polylactic acid composite material, the content of the dynamic bond polyurethane is 5 to 50 wt%, preferably 15 to 30 wt%;

[0011] The polylactic acid may be commercially available industrial grade polylactic acid.

[0012] The above-mentioned dynamic bond-containing polyurethane provided by the present invention is the reaction product of a macromolecular polyol, an isocyanate compound, a dynamic bond-containing chain extender and an optionally added small molecule polyol chain extender.

[0013] In the polyurethane containing dynamic bonds:

[0014] The macromolecular polyol is selected from at least one of polyester polyols, polyether polyols, polyolefin polyols, polysiloxane polyols, or derivatives thereof, preferably non-bio-based polyester polyols (polycaprolactone, polypropylene glycol, polyethylene glycol, polybutylene adipate, polypropylene adipate, polyethylene adipate, polypropylene succinate, polyethylene succinate, etc.) or bio-based polyester polyols (Priplast 3197, Priplast 3238, Priplast 3294, etc.), non-bio-based polyether polyols (polytetrahydrofuran, polyethylene glycol, polypropylene glycol, etc.) or bio-based polyether polyols (polytrimethylene ether glycol, pripol 2033, etc.), non-bio-based polyolefin polyols (hydroxy-terminated butylbenzene polyols, hydroxy-terminated butadiene polyols, etc.), bio-based polyolefin polyols (polyfarnesene polyols, etc.), polysiloxane polyols or at least one of their derivatives; wherein the derivatives are multifunctional (e.g., amino, thiol) derivatives of the above-mentioned macromolecular polyols, such as macromolecular polyol derivatives with amino or thiol groups;

[0015] The number average molecular weight of the macromolecular polyol is 500 to 4000, preferably 1000 to 2000;

[0016] The isocyanate compound is selected from at least one of toluene diisocyanate, diphenylmethane diisocyanate, hexamethylene diisocyanate, tetramethyl-m-xylylene diisocyanate, trimethyl-1,6-hexamethylene diisocyanate, isophorone diisocyanate, dimethyl biphenyl diisocyanate, 1,5-naphthalene diisocyanate, p-phenylene diisocyanate, 4,4'-dicyclohexylmethane diisocyanate, 1,4-cyclohexane diisocyanate, norbornane diisocyanate, methylcyclohexyl diisocyanate, pentamethylene diisocyanate, lysine diisocyanate, polymethylene polyphenyl isocyanate, and toluene diisocyanate dimer, preferably at least one of pentamethylene diisocyanate and hexamethylene diisocyanate;

[0017] The dynamic bond-containing chain extender is a compound containing at least one of a dithioacetal bond, a disulfide bond, an imine bond, a β-hydroxy ester bond, a boric ester bond, a silyl ether bond, and a cyclic acetal bond, or a mixture thereof;

[0018] The small molecule polyol chain extender is selected from at least one of ethylene glycol, diethylene glycol, propylene glycol, glycerol, butylene glycol, pentaerythritol, hexylene glycol, neopentyl glycol, trimethylolpropane, xylitol, sorbitol, and castor oil, preferably at least one of butylene glycol and trimethylolpropane;

[0019] An antioxidant is also added to the dynamic bond-containing polyurethane. Preferably, the antioxidant is selected from at least one of triethylene glycol bis[β-(3-tert-butyl-4-hydroxy-5-methylphenyl) propionate] (Anti-245), pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate] (Anti-1010), and 1,3,5-trimethyl-2,4,6-(3,5-di-tert-butyl-4-hydroxybenzyl) benzene (Anti-1030).

[0020] The second object of the present invention is to provide a method for preparing the above-mentioned dynamically cross-linked polyurethane toughened polylactic acid composite material, comprising: melt blending the polylactic acid and the polyurethane containing dynamic bonds to obtain the polylactic acid composite material toughened by the dynamic cross-linked polyurethane. The polylactic acid and the polyurethane containing dynamic bonds are pre-treated to remove water; the melt blending conditions are: the melt blending temperature is 165 to 200°C, preferably 170 to 180°C; the melt blending speed is 30 to 200 rpm, preferably 50 to 100 rpm; the melt blending time is 5 to 30 minutes, preferably 5 to 10 minutes.

[0021] In the preparation method of the above-mentioned polylactic acid composite material, the preparation method of the polyurethane containing dynamic bonds comprises:

[0022] Method 1: After prepolymerization of a macromolecular polyol, an isocyanate compound, and a catalyst, a dynamic bond-containing chain extender and an optional small molecule polyol chain extender are added to carry out a chain extension reaction, and the dynamic bond-containing polyurethane is obtained after curing; or

[0023] Method 2: stirring and reacting a macromolecular polyol, an isocyanate compound, a dynamic bond-containing chain extender and an optionally added small molecule polyol chain extender under the action of a catalyst, and curing to obtain the dynamic bond-containing polyurethane.

[0024] In the above-mentioned preparation method of the polyurethane containing dynamic bonds:

[0025] Based on 1 mole of the macromolecular polyol, the isocyanate compound is 1 to 7 moles, and the weight of the chain extender is 0.01 to 6 moles; preferably, based on 1 mole of the macromolecular polyol, the isocyanate compound is 1.2 to 3.5 moles, and the total amount of the chain extender is 0.2 to 2.5 moles;

[0026] The dynamic bond-containing chain extender accounts for 5 to 100 mol%, preferably 5 to 95 mol% of the total amount of the chain extender;

[0027] The catalyst is selected from at least one of an organic tin catalyst, an organic zinc catalyst, and an organic bismuth catalyst, preferably at least one of stannous octoate, dibutyltin diacetate, dibutyltin dilaurate, di(dodecylthio)dibutyltin, zinc isooctanoate, and bismuth isooctanoate;

[0028] The catalyst is used in an amount of 0.01 to 0.5 wt% of the total amount of the macromolecular polyol, isocyanate compound and chain extender;

[0029] An antioxidant is also added to the reaction. Preferably, the amount of the antioxidant is 0.1-0.5 wt % of the total amount of the macromolecular polyol, isocyanate compound and chain extender.

[0030] In the above-mentioned preparation method of the dynamic bond-containing polyurethane:

[0031] The macromolecular polyol is pre-treated to remove water, for example, removing water for 2 hours at 110°C, -0.05MPa, and 150rpm stirring conditions;

[0032] The conditions of the prepolymerization reaction in the method 1 are: the prepolymerization reaction temperature is 80-100° C., and the prepolymerization reaction time is 1-5 hours;

[0033] The conditions of the chain extension reaction in the method 1 are: the chain extension reaction temperature is 80-100° C., and the chain extension reaction time is 5-60 min;

[0034] The reaction conditions in the second method are: reaction temperature is 60-80°C, reaction time is 0.05-1h;

[0035] The curing conditions in the method 1 or the method 2 are: the curing temperature is 100 to 120° C., and the curing time is 6 to 24 hours.

[0036] In the above-mentioned preparation method of the polyurethane containing dynamic bonds, the preparation method of the dynamic bond-containing chain extender comprises: stirring and reacting a polyaldehyde compound and a polyamine compound at 70 to 100° C. in a protective gas atmosphere for 20 to 60 minutes, and then adding a carbonate compound and continuing the reaction for 1 to 3 hours to obtain the dynamic bond-containing chain extender; preferably,

[0037] The polyaldehyde compound is selected from at least one of malondialdehyde, benzaldehyde, succinaldehyde, terephthalaldehyde and trimesic acid;

[0038] The polyamine compound is selected from at least one of ethylenediamine, propylenediamine and butylenediamine;

[0039] The carbonate compound is selected from at least one of ethylene carbonate and propylene carbonate;

[0040] The molar ratio of the polyaldehyde compound, the polyamine compound and the carbonate compound is 1:2:1, wherein the aldehyde compound is calculated by the molar number of aldehyde groups, the polyamine compound is calculated by the molar number of amino groups, and the carbonate compound is calculated by the molar number of carbonate groups.

[0041] The present invention adopts a one-step method or a two-step method (prepolymer method) to first prepare a dynamically cross-linked polyurethane elastomer, and then prepares a high-toughness polylactic acid composite material containing dynamic bonds by high-temperature melt blending. By adjusting the polyurethane composition, such as the type and molecular weight of the polyol (500-4000), the hard segment content 10-50wt%, the cross-linking agent structure type and dosage, the polyurethane dosage (5wt%-50wt%) and other parameters, the notched impact strength of the obtained polylactic acid composite material can reach 84.42KJ / m 2 , the shrinkage rate can be maintained at 0.75%, which is close to that of pure polylactic acid and is significantly better than that of polylactic acid composites modified with no dynamic bond material. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] Figure 1 The complex viscosity-angular frequency curves of Comparative Example 1, Comparative Example 3 and Example 6. DETAILED DESCRIPTION

[0043] The present invention is described in detail below in conjunction with specific embodiments. It is necessary to point out that the following embodiments are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made to the present invention by those skilled in the art based on the contents of the present invention still fall within the scope of protection of the present invention.

[0044] The test instruments and test conditions used in the examples are as follows:

[0045] Notched impact strength test: refer to GB / T 1843-2008 for testing, and the instrument used is a cantilever beam impact testing machine.

[0046] Shrinkage test: Compare the actual area D2 and the mold area D1 of the notched impact specimen after injection molding. Shrinkage = (D1-D2) / D1*100%.

[0047] Complex viscosity test: Use a rotational rheometer at 180°C, 1% strain, 25mm parallel plate size, 1mm gap, test complex viscosity values ​​in the range of 0.1rad / s to 100rad / s, and take 30 points.

[0048] The raw materials used in the examples and comparative examples, unless otherwise specified, are disclosed in the prior art, for example, they can be directly purchased or prepared according to the preparation methods disclosed in the prior art.

[0049] Comparative Example 1

[0050] The dried polylactic acid was added into an internal mixer and melt-treated at 180° C. and 100 rpm for 10 minutes.

[0051] Comparative Example 2

[0052] Preparation of polyurethane

[0053] The dehydrated bio-based polyol polytrimethyl ether glycol (number average molecular weight of 1000, 1 mol, dehydrated in advance at 110°C, -0.05MPa, 150rpm for 2 hours), pentamethylene diisocyanate (1.73 mol), chain extender 1,4-butanediol (0.73 mol), catalyst dibutyltin dilaurate (0.03wt%), antioxidant anti-1010 (0.03wt%) were directly stirred and mixed at 70°C for 6 minutes, and then cured in an oven at 100°C for 12 hours to obtain polyurethane TPU-1. The obtained polyurethane TPU-1 has a hard segment content of 25wt% and an R value of 1.

[0054] Preparation of polylactic acid composite materials

[0055] The dried polylactic acid (75wt%) was added into an internal mixer and melt-treated for 3 minutes at 180°C and 100 rpm. The cured and dried polyurethane TPU-1 (25wt%) was added into the internal mixer and melt-mixed for 7 minutes at 100 rpm to obtain a polylactic acid composite material.

[0056] Comparative Example 3

[0057] Preparation of polyurethane

[0058] Polytrimethylene ether glycol (1 mol, number average molecular weight of 1000) was dehydrated for 2 hours at 110°C, -0.05 MPa, 150 rpm stirring conditions, and the dehydrated polytrimethylene ether glycol, pentamethylene diisocyanate (1.735 mol), catalyst dibutyltin dilaurate (0.03 wt%), and antioxidant anti-1010 (0.03 wt%) were prepolymerized at 90°C for 3 hours, and then trimethylolpropane (0.49 mol) was added and stirred rapidly for 25 minutes, and the polyurethane sample was taken out and cured in an oven at 100°C for 12 hours to obtain polyurethane TPU-2. The hard segment content of the obtained polyurethane TPU-2 is 25 wt%, and the R value is 1.

[0059] Preparation of polylactic acid composite materials

[0060] The dried polylactic acid (75wt%) was added into an internal mixer and melt-treated for 3 minutes at 180°C and 100 rpm. The cured and dried polyurethane TPU-2 (25wt%) was added into the internal mixer and melt-mixed for 7 minutes at 100 rpm to obtain a polylactic acid composite material.

[0061] Example 1

[0062] Preparation of chain extenders containing dynamic bonds

[0063] Terephthalaldehyde (1 mol) and ethylenediamine (2 mol) were stirred at 80° C. in a nitrogen atmosphere for 30 minutes, and then ethylene carbonate (2 mol) was added and the reaction was continued for 2 hours to obtain a dynamic bond-containing chain extender, which was recorded as chain extender D1.

[0064] Preparation of polyurethane

[0065] Polytrimethylene ether glycol (1 mol, number average molecular weight of 1000) was dehydrated for 2 hours at 110°C, -0.05 MPa, 150 rpm stirring conditions, and the dehydrated polytrimethylene ether glycol, pentamethylene diisocyanate (1.40 mol), catalyst dibutyltin dilaurate (0.03 wt%), and antioxidant anti-1010 (0.03 wt%) were prepolymerized at 90°C for 3 hours, followed by the addition of trimethylolpropane (0.12 mol) and chain extender D1 (0.28 mol, accounting for 70 mol% of the total amount of the chain extender) and rapid stirring for 25 minutes, and the polyurethane sample was taken out and cured in an oven at 100°C for 12 hours to obtain polyurethane TPU-3. The obtained polyurethane TPU-3 has a hard segment content of 25 wt% and an R value of 1.

[0066] Preparation of polylactic acid composite materials

[0067] The dried polylactic acid (93wt%) was added into an internal mixer and melt-treated for 3 minutes at 180°C and 100 rpm. The cured and dried polyurethane TPU-3 (7wt%) was added into the internal mixer and melt-mixed for 7 minutes at 100 rpm to obtain a polylactic acid composite material.

[0068] Example 2

[0069] Preparation of polylactic acid composite materials

[0070] The dried polylactic acid (85wt%) was added to an internal mixer and melt-treated at 180°C and 100 rpm for 3 minutes; the cured and dried polyurethane TPU-3 (15wt%, prepared by the same method as in Example 1) was added to the internal mixer and melt-mixed at 100 rpm for 7 minutes to obtain a polylactic acid composite material.

[0071] Example 3

[0072] Preparation of polylactic acid composite materials

[0073] The dried polylactic acid (70 wt %) was added to an internal mixer and melt-treated at 180° C. and 100 rpm for 3 minutes. The cured and dried polyurethane TPU-3 (30 wt %, prepared by the same method as in Example 1) was added to the internal mixer and melt-mixed at 100 rpm for 7 minutes to obtain a polylactic acid composite material.

[0074] Example 4

[0075] Preparation of polylactic acid composite materials

[0076] The dried polylactic acid (50wt%) was added to an internal mixer and melt-treated at 180°C and 100 rpm for 3 minutes; the cured and dried polyurethane TPU-3 (50wt%, prepared by the same method as in Example 1) was added to the internal mixer and melt-mixed at 100 rpm for 7 minutes to obtain a polylactic acid composite material.

[0077] Example 5

[0078] Preparation of polyurethane

[0079] Polytrimethylene ether glycol (1 mol, number average molecular weight of 1000) was dehydrated for 2 hours at 110°C, -0.05 MPa, 150 rpm stirring conditions, and the dehydrated polytrimethylene ether glycol, pentamethylene diisocyanate (1.6 mol), catalyst dibutyltin dilaurate (0.03 wt%), and antioxidant anti-1010 (0.03 wt%) were prepolymerized at 90°C for 3 hours, followed by the addition of trimethylolpropane (0.57 mol) and chain extender D1 (0.03 mol, accounting for 5 mol% of the total amount of the chain extender) and rapid stirring for 25 minutes, and the polyurethane sample was taken out and cured in an oven at 100°C for 12 hours to obtain polyurethane TPU-4. The obtained polyurethane TPU-4 has a hard segment content of 25 wt% and an R value of 1.

[0080] Preparation of polylactic acid composite materials

[0081] The dried polylactic acid (75wt%) was added into an internal mixer and melt-treated at 180°C and 100 rpm for 3 minutes; the cured and dried polyurethane TPU-4 (25wt%) was added into the internal mixer and melt-mixed at 100 rpm for 7 minutes.

[0082] Example 6

[0083] Preparation of polyurethane

[0084] Polytrimethylene ether glycol (1 mol, number average molecular weight of 1000) was dehydrated for 2 hours at 110°C, -0.05 MPa, 150 rpm stirring conditions, and the dehydrated polytrimethylene ether glycol, pentamethylene diisocyanate (1.47 mol), catalyst dibutyltin dilaurate (0.03 wt%), and antioxidant anti-1010 (0.03 wt%) were prepolymerized at 90°C for 3 hours, followed by the addition of trimethylolpropane (0.282 mol) and chain extender D1 (0.188 mol, accounting for 40 mol% of the total amount of the chain extender) and rapid stirring for 25 minutes, and the polyurethane sample was taken out and cured in an oven at 100°C for 12 hours to obtain polyurethane TPU-5. The obtained polyurethane TPU-5 has a hard segment content of 25 wt% and an R value of 1.

[0085] Preparation of polylactic acid composite materials

[0086] The dried polylactic acid (75wt%) was added into an internal mixer and melt-treated at 180°C and 100 rpm for 3 minutes; the cured and dried polyurethane TPU-5 (25wt%) was added into an internal mixer and melt-mixed at 100 rpm for 7 minutes.

[0087] Example 7

[0088] Preparation of polyurethane

[0089] Polytrimethylene ether glycol (1 mol, number average molecular weight of 1000) was dehydrated for 2 hours at 110°C, -0.05 MPa, 150 rpm stirring conditions, and the dehydrated polytrimethylene ether glycol, pentamethylene diisocyanate (1.36 mol), catalyst dibutyltin dilaurate (0.03 wt%), and antioxidant anti-1010 (0.03 wt%) were prepolymerized at 90°C for 3 hours, followed by the addition of trimethylolpropane (0.036 mol) and chain extender D1 (0.324 mol, accounting for 90 mol% of the total amount of the chain extender) and rapid stirring for 25 minutes, and the polyurethane sample was taken out and cured in an oven at 100°C for 12 hours to obtain polyurethane TPU-6. The obtained polyurethane TPU-6 has a hard segment content of 25 wt% and an R value of 1.

[0090] Preparation of polylactic acid composite materials

[0091] The dried polylactic acid (75wt%) was added into an internal mixer and melt-treated at 180°C and 100 rpm for 3 minutes; the cured and dried polyurethane TPU-6 (25wt%) was added into the internal mixer and melt-mixed at 100 rpm for 7 minutes.

[0092] Example 8

[0093] Preparation of polyurethane

[0094] Polytrimethylene ether glycol (1 mol, number average molecular weight of 1000) was dehydrated for 2 hours at 110°C, -0.05 MPa, 150 rpm stirring conditions, and the dehydrated polytrimethylene ether glycol, pentamethylene diisocyanate (2.88 mol), catalyst dibutyltin dilaurate (0.03 wt%), and antioxidant anti-1010 (0.03 wt%) were prepolymerized at 90°C for 3 hours, followed by the addition of trimethylolpropane (0.564 mol) and chain extender D1 (1.316 mol, accounting for 70 mol% of the total amount of the chain extender) and rapid stirring for 25 minutes, and the polyurethane sample was taken out and cured in an oven at 100°C for 12 hours to obtain polyurethane TPU-7. The obtained polyurethane TPU-7 has a hard segment content of 50 wt% and an R value of 1.

[0095] Preparation of polylactic acid composite materials

[0096] The dried polylactic acid (75wt%) was added into an internal mixer and melt-treated at 180°C and 100 rpm for 3 minutes. The cured and dried polyurethane TPU-7 (25wt%) was added into an internal mixer and melt-mixed at 100 rpm for 7 minutes.

[0097] Example 9

[0098] Preparation of chain extenders containing dynamic bonds

[0099] Trimellitic acid aldehyde (1 mol) and ethylenediamine (3 mol) were stirred at 80° C. in a nitrogen atmosphere for 30 minutes, and then ethylene carbonate (3 mol) was added and the reaction was continued for 2 hours to obtain a dynamic bond-containing chain extender, which was recorded as chain extender D2.

[0100] Preparation of polyurethane

[0101] Polytrimethylene ether glycol (1 mol, number average molecular weight of 1000) was dehydrated for 2 hours at 110°C, -0.05 MPa, 150 rpm stirring conditions, and the dehydrated polytrimethylene ether glycol, pentamethylene diisocyanate (1.61 mol), catalyst dibutyltin dilaurate (0.03 wt%), and antioxidant anti-1010 (0.03 wt%) were prepolymerized at 90°C for 3 hours, followed by the addition of butanediol (0.549 mol) and chain extender D2 (0.061 mol, accounting for 10 mol% of the total amount of chain extender) and rapid stirring for 25 minutes, and the polyurethane sample was taken out and cured in an oven at 100°C for 12 hours to obtain polyurethane TPU-8. The obtained polyurethane TPU-8 has a hard segment content of 25 wt% and an R value of 1.

[0102] Preparation of polylactic acid composite materials

[0103] The dried polylactic acid (75wt%) was added into an internal mixer and melt-treated at 180°C and 100 rpm for 3 minutes. The cured and dried polyurethane TPU-8 (25wt%) was added into an internal mixer and melt-mixed at 100 rpm for 7 minutes.

[0104] Example 10

[0105] Preparation of polyurethane

[0106] Polytrimethylene ether glycol (1 mol, number average molecular weight of 1000) was dehydrated for 2 hours at 110°C, -0.05 MPa, 150 rpm stirring conditions, and the dehydrated polytrimethylene ether glycol, pentamethylene diisocyanate (1.563 mol), catalyst dibutyltin dilaurate (0.03 wt%), and antioxidant anti-1010 (0.03 wt%) were prepolymerized at 90°C for 3 hours, followed by the addition of butanediol (0.47855 mol) and chain extender D2 (0.08445 mol, accounting for 15 mol% of the total amount of the chain extender) and rapid stirring for 25 minutes, and the polyurethane sample was taken out and cured in an oven at 100°C for 12 hours to obtain polyurethane TPU-9. The obtained polyurethane TPU-9 has a hard segment content of 25 wt% and an R value of 1.

[0107] Preparation of polylactic acid composite materials

[0108] The dried polylactic acid (75wt%) was added into an internal mixer and melt-treated at 180°C and 100 rpm for 3 minutes. The cured and dried polyurethane TPU-9 (25wt%) was added into an internal mixer and melt-mixed at 100 rpm for 7 minutes.

[0109] Embodiment 11

[0110] Preparation of polyurethane

[0111] Polytrimethylene ether glycol (1 mol, number average molecular weight of 1000) was dehydrated for 2 hours at 110°C, -0.05 MPa, 150 rpm stirring conditions, and the dehydrated polytrimethylene ether glycol, pentamethylene diisocyanate (1.455 mol), catalyst dibutyltin dilaurate (0.03 wt%), and antioxidant anti-1010 (0.03 wt%) were prepolymerized at 90°C for 3 hours, followed by the addition of butanediol (0.3185 mol) and chain extender D2 (0.1365 mol, accounting for 30 mol% of the total amount of the chain extender) and rapid stirring for 25 minutes, and the polyurethane sample was taken out and cured in an oven at 100°C for 12 hours to obtain polyurethane TPU-10. The obtained polyurethane TPU-10 has a hard segment content of 25 wt% and an R value of 1.

[0112] Preparation of polylactic acid composite materials

[0113] The dried polylactic acid (75wt%) was added into an internal mixer and melt-treated at 180°C and 100 rpm for 3 minutes. The cured and dried polyurethane TPU-10 (25wt%) was added into an internal mixer and melt-mixed at 100 rpm for 7 minutes.

[0114] The polyurethane composite materials prepared in Examples 1 to 11 and Comparative Examples 1 to 3 were subjected to notched impact strength tests. The test results are shown in Table 1.

[0115] Table 1. Notched impact strength test results

[0116] <![CDATA[Notched impact strength (KJ / m 2 )]]> Shrinkage rate (%) Comparative Example 1 3.21 0.71 Comparative Example 2 12.54 0.76 Comparative Example 3 30.56 15.36 Example 1 18.48 0.82 Example 2 45.25 0.86 Example 3 72.84 0.99 Example 4 84.42 1.14 Example 5 40.78 1.05 Example 6 53.65 0.98 Example 7 52.36 0.87 Example 8 69.25 1.06 Example 9 49.58 0.88 Example 10 56.35 0.82 Embodiment 11 60.47 0.75

[0117] Depend on Figure 1 It can be seen that under the same polyurethane filling amount, the complex viscosity of Example 6 with dynamic bonds is significantly lower than that of Comparative Example 3 without dynamic bonds, and is close to that of pure polylactic acid (Comparative Example 1), which is beneficial to reducing the dimensional shrinkage during processing. From the results in Table 1, it can be seen that compared with Comparative Examples 1 to 3, changing the composition (hard segment content, dynamic bond chain extender ratio, etc.) and dosage of the dynamically cross-linked polyurethane in Examples 1 to 11 can effectively improve the notched impact strength of the polylactic acid composite material. At the same time, the presence of dynamic bonds in the polyurethane makes the cross-linked network dynamically reversible, which effectively reduces the dimensional shrinkage of the composite material during processing, which is beneficial to the precise processing of the product size.

Claims

1. A dynamically cross-linked polyurethane toughened polylactic acid composite material, comprising: A mixture of polyurethane containing dynamic bonds and polylactic acid and / or a reaction product thereof, wherein the hard segment content of the polyurethane containing dynamic bonds is 10-50wt%, and the content of the polyurethane containing dynamic bonds is 5-50wt%; the polyurethane containing dynamic bonds is the reaction product of a macromolecular polyol, an isocyanate compound, a dynamic bond-containing chain extender and an optionally added small molecule polyol chain extender, and the number average molecular weight of the macromolecular polyol is 500-4000; the preparation method of the dynamic bond-containing chain extender comprises: stirring a polyaldehyde compound and a polyamine compound at 70-100° C. and a protective gas atmosphere for 20-60 minutes, and continuously adding a carbonate compound and continuously reacting for 1-3 hours to obtain the dynamic bond-containing chain extender.

2. The polylactic acid composite material according to claim 1, characterized in that: The hard segment content of the dynamic bond-containing polyurethane is 20-30wt%; and / or, In the polylactic acid composite material, the content of the dynamic bond polyurethane is 15-30 wt%.

3. The composite material according to claim 1, characterized in that The macromolecular polyol is selected from at least one of polypropylene glycol, polyethylene glycol, polytetrahydrofuran, polytrimethylene ether glycol, hydroxy-terminated butylbenzene polyol, hydroxy-terminated butadiene polyol, polyfarnesene polyol, polysiloxane polyol, or derivatives thereof; and / or, The number average molecular weight of the macromolecular polyol is 1000-2000; and / or, The isocyanate compound is selected from at least one of toluene diisocyanate, diphenylmethane diisocyanate, hexamethylene diisocyanate, tetramethyl-m-xylylene diisocyanate, trimethyl-1,6-hexamethylene diisocyanate, isophorone diisocyanate, dimethyl biphenyl diisocyanate, 1,5-naphthalene diisocyanate, p-phenylene diisocyanate, 4,4'-dicyclohexylmethane diisocyanate, 1,4-cyclohexane diisocyanate, norbornane diisocyanate, methylcyclohexyl diisocyanate, pentamethylene diisocyanate, lysine diisocyanate, polymethylene polyphenyl isocyanate, and toluene diisocyanate dimer; and / or, The small molecule polyol chain extender is selected from at least one of ethylene glycol, diethylene glycol, propylene glycol, glycerol, butylene glycol, pentaerythritol, hexylene glycol, neopentyl glycol, trimethylolpropane, xylitol, sorbitol and castor oil; and / or, An antioxidant is also added into the dynamic bond-containing polyurethane.

4. The composite material according to claim 3, characterized in that The isocyanate compound is selected from at least one of pentamethylene diisocyanate and hexamethylene diisocyanate; and / or, The small molecule polyol chain extender is selected from at least one of butanediol and trimethylolpropane; and / or, The antioxidant is selected from at least one of triethylene glycol bis[β-(3-tert-butyl-4-hydroxy-5-methylphenyl) propionate], pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, and 1,3,5-trimethyl-2,4,6-(3,5-di-tert-butyl-4-hydroxybenzyl)benzene.

5. A method for preparing the polylactic acid composite material toughened by dynamically cross-linked polyurethane according to any one of claims 1 to 4, comprising: The polylactic acid and the polyurethane containing dynamic bonds are melt-blended to obtain the polylactic acid composite material toughened by the dynamic cross-linking polyurethane.

6. The preparation method according to claim 5, characterized in that: The conditions of the melt blending are: The melt blending temperature is 165-200°C; and / or, The melt blending speed is 30 to 200 rpm; and / or, The melt blending time is 5 to 30 minutes.

7. The preparation method according to claim 6, characterized in that: The conditions of the melt blending are: The melt blending temperature is 170-180°C; and / or, The melt blending speed is 50 to 100 rpm; and / or, The melt blending time is 5 to 10 minutes.

8. The preparation method according to claim 5, characterized in that: The preparation method of the dynamic bond-containing polyurethane comprises: Method 1: After prepolymerization of a macromolecular polyol, an isocyanate compound, and a catalyst, a dynamic bond-containing chain extender and an optional small molecule polyol chain extender are added to carry out a chain extension reaction, and after curing, the dynamic bond-containing polyurethane is obtained; Method 2: stirring and reacting a macromolecular polyol, an isocyanate compound, a dynamic bond-containing chain extender and an optionally added small molecule polyol chain extender under the action of a catalyst, and curing to obtain the dynamic bond-containing polyurethane.

9. The preparation method according to claim 8, characterized in that: Based on 1 molar part of the macromolecular polyol, the isocyanate compound is 1 to 7 molar parts, and the total amount of the chain extender is 0.01 to 6 molar parts; and / or, The dynamic bond-containing chain extender accounts for 5 to 100 mol% of the total chain extender; and / or, The catalyst is selected from at least one of an organic tin catalyst, an organic zinc catalyst, and an organic bismuth catalyst; and / or, The amount of the catalyst is 0.01-0.5wt% of the total amount of the macromolecular polyol, isocyanate compound and chain extender; and / or, An antioxidant is also added to the reaction.

10. The preparation method according to claim 9, characterized in that: Based on 1 molar part of the macromolecular polyol, the isocyanate compound is 1.2 to 3.5 molar parts, and the total amount of the chain extender is 0.2 to 2.5 molar parts; and / or, The dynamic bond-containing chain extender accounts for 5 to 95 mol% of the total amount of the chain extender; and / or, The catalyst is selected from at least one of stannous octoate, dibutyltin diacetate, dibutyltin dilaurate, di(dodecylthio)dibutyltin, zinc isooctanoate, and bismuth isooctanoate; and / or, The amount of the antioxidant is 0.1-0.5 wt % of the total amount of the macromolecular polyol, the isocyanate compound and the chain extender.

11. The preparation method according to claim 8, characterized in that: The conditions of the prepolymerization reaction in the method 1 are: the prepolymerization reaction temperature is 80-100° C., and the prepolymerization reaction time is 1-5 hours; and / or, The conditions of the chain extension reaction in the method 1 are: the chain extension reaction temperature is 80-100° C., and the chain extension reaction time is 5-60 min; and / or, The reaction conditions in the second method are: reaction temperature is 60-80°C, reaction time is 0.05-1h; and / or, The curing conditions in the method 1 or the method 2 are: the curing temperature is 100-120° C., and the curing time is 6-24 hours.

12. The preparation method according to claim 8, characterized in that: The polyaldehyde compound is selected from at least one of malondialdehyde, succinaldehyde, terephthalaldehyde and trimesic acid; and / or, The polyamine compound is selected from at least one of ethylenediamine, propylenediamine and butylenediamine; and / or, The carbonate compound is selected from at least one of ethylene carbonate and propylene carbonate; and / or, The molar ratio of the polyaldehyde compound, the polyamine compound and the carbonate compound is 1:2:1, wherein the aldehyde compound is calculated by the molar number of aldehyde groups, the polyamine compound is calculated by the molar number of amino groups, and the carbonate compound is calculated by the molar number of carbonate groups.

Citation Information

Patent Citations

  • High-toughness polylactic acid / crosslinked polyurethane compound and preparation method thereof

    CN103450649A

  • Vegetable oil derivative reactive blending method for preparing high-impacting toughness polylactic acid compound

    CN108707322A

  • High-toughness bio-based polylactic acid / reactive modified rubber thermoplastic vulcanized rubber blending material and secondary reaction extrusion preparation method thereof

    CN109401243A

  • Modified gutta-percha / polylactic acid thermoplastic elastomer with shape memory effect and preparation method thereof

    CN112175365A

  • Polyether polyurethane elastomer toughened polylactic acid alloy and preparation method thereof

    CN102181136A